If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 3(2x + -7) = 15x + -17 Reorder the terms: 4 + 3(-7 + 2x) = 15x + -17 4 + (-7 * 3 + 2x * 3) = 15x + -17 4 + (-21 + 6x) = 15x + -17 Combine like terms: 4 + -21 = -17 -17 + 6x = 15x + -17 Reorder the terms: -17 + 6x = -17 + 15x Add '17' to each side of the equation. -17 + 17 + 6x = -17 + 17 + 15x Combine like terms: -17 + 17 = 0 0 + 6x = -17 + 17 + 15x 6x = -17 + 17 + 15x Combine like terms: -17 + 17 = 0 6x = 0 + 15x 6x = 15x Solving 6x = 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 6x + -15x = 15x + -15x Combine like terms: 6x + -15x = -9x -9x = 15x + -15x Combine like terms: 15x + -15x = 0 -9x = 0 Divide each side by '-9'. x = 0 Simplifying x = 0
| 4.5-(-b)=0.4 | | 40+40j=2(-4j-13) | | 6(3w-4)=2(7w-4) | | -4(3m+5)=-2(m-2) | | 3(2m-3)=5(m+1) | | 2(x+1)=-3(x-2) | | -3x=4(3x-2)+1 | | -28(-28-2)=-28+28 | | 25x-8x=34 | | 18-6x=36 | | 2x+(-2x)=x+28 | | (x+3)+(x+5)+8=33 | | (a+8)+(5a-7)= | | 2x+5x-x=36 | | 5-5x=14-8x | | (a+8)+(5a-7)+(a+3)+(2a-5)+(a+1)= | | -8b-15+6b=12 | | 2(3y-6)=24 | | 4(2x-7)=36 | | 3x+5+6x=32 | | -4n+7+6n=-19 | | 3x+4x-7=21 | | -3n+9+5n=-17 | | 2x+9x-2=31 | | 3(n+5)-8=10n | | 21a+17+15a=-48 | | -6(5-2x)=54 | | 6(y+2)-4=10 | | 7-3x=x-4(2x+x) | | -8(4+9x)=7(-2-x) | | -2.2y=11.6+262.6 | | 7-(x-3)=-4 |